"We invited the disease to come to us": neoliberal public health discourse and local understanding of non-communicable disease causation in Fiji. Issue 5 (20th October 2018) - Phillips, Tarryn; McMichael, Celia; O'Keefe, Michael
Abstract: Rates of non-communicable diseases (NCDs) are increasing globally, particularly amongst low- and middle-income countries. Critical public health scholars have argued that while political and socio-economic factors shape health outcomes within particular environments, neoliberal public health efforts tend to emphasise individual responsibility to avoid behavioural risks and 'choose' health. Yet there is little analysis of how these discourses about personal responsibility for NCDs are internalised, resisted or adapted by target populations in the Global South. This paper does so by examining local understandings of causal attribution for NCDs in Fiji. Data are drawn from qualitative research with outpatients, villagers and health care staff on the island of Ovalau ( n = 68). Residents deem individual choices to be the principal cause of poor health outcomes. While they mention some social, historical and spiritual determinants of NCDs, community members have internalised a neoliberal governmentality, in which individuals are held morally accountable for preventing disease. Moreover, these messages about NCDs intersect with other discourses that promote personal responsibility in Fijian society – such as colonial legacies, traditional gender roles and Christianity. This local adaptation of neoliberalism reproduces historically entrenched stereotypes about Indigenous Fijians as irresponsible citizens, and obscures community recognition and response regarding the structural determinants of the NCD problem.